Study of the Characteristics and Comprehensive Fuzzy Assessment of Indoor Air Chemical Contamination in Public Buildings - Xiguan Liang; Zhisheng Li; Huagang Zhang; Xinru Hong (Frontiers Media S.A., 2021)
Quality-of-life is improving daily with continuous improvements in urban modernization, which necessitates more stringent requirements for indoor air quality. Fuzzy assessment enables us to obtain the grade of the evaluation object by compound calculation with the help of membership function and weight coefficient, overcoming the limitations of traditional methods applied to develop environmental quality indices. First, this study continuously measured SO2, O3, NO2, NO, CO, CO2, PM10, PM2.5, and other chemical pollutants during the daytime operating hours of a library and a canteen. We analyzed the concentration distributions of the particles in the air were discussed based on 31 different particle diameters. Finally, the experimental data in department store and waiting hall were analyzed by fuzzy evaluation, with the following results. (1) The library and canteen PM10 concentrations peaked at 07:45 in the morning and was elevated during the afternoon (48.9 and 59 μg/m3, respectively). (2) The Pearson correlation coefficient of the PM10 and PM2.5 concentrations in the library was 0.98. PM10 and SO2 in the canteen were negatively correlated, with a correlation coefficient of −0.65. PM2.5 and PM1 were always highly positively correlated. (3) The high concentration of particles in the library was associated with the small particle size range (0.25~0.45 μm). (4) By applying the fuzzy comprehensive evaluation method, the library grade evaluation was the highest level, and the waiting hall was the lowest. This study enhances our understanding of the indoor chemical contamination relationships for public buildings and highlights the urgent need for improving indoor air quality.